Massage on meridians combined with Traditional Chinese Medicine hot compress for pain in a patient undergoing surgery for mixed hemorrhoids and related nursing management (经穴推拿联合中药热熨敷治疗1例混合痔术后疼痛患者的护理体会) - DONG Yuxia (董玉霞); E Haiyan (鄂海燕); WANG Yali (王亚丽); WEI Yongchun (魏永春); JIANG Jing (姜婧) (中西医结合护理)
This paper reviewed the clinical data and nursing measures of a patients receiving Massage on meridians combined with Traditional Chinese Medicine hot compress for pain after surgery for mixed hemorrhoids. According to the standards of Traditional Chinese Medicine Nursing Techniques, Massage on meridians combined with Traditional Chinese Medicine hot compress on Baliao acupoints were performed to relive the postoperative pain and improve treatment compliance of patients. (本文总结1例混合痔术后疼痛患者运用经穴推拿联合中药热熨敷治疗的护理经验。根据《中医护理技术规范》对患者进行经穴推拿手法联合中药热熨敷八髎穴, 有效改善混合痔患者术后疼痛症状, 提高患者对治疗、护理的依从性, 对进一步提高患者的生活质量有积极作用。)